Frugal innovation : a proposal of an instrument to measurement - Rossetto, Dennys Eduardo (2018)
In both the academy and the press, Frugal Innovation has gained more space and attention from researchers and managers, mainly as an alternative to competitiveness in times of crisis and increasingly scarce resources. Despite the growing number of published articles on frugal innovation, there is still a lack of tools that allow mediation and quantification of this phenomenon to allow more precise and quantifiable studies to be carried out. In addition, due to the broad concepts of Frugal Innovation still in the process of consolidation, it would be very useful for managers and entrepreneurs an instrument that allows identifying and guiding companies that want guidelines for the development of frugal offers, besides constituting a significant theoretical contribution . In this thesis, we propose a scale to identify and measure frugal innovation, presenting the results of five data collection in three different countries (Brazil, USA and India), with the whole development process, the refinement of items through an Exploratory EFA), Confirmation Factor Analysis (CFA) and final validation of the scale based on the company's 1130 data. A broad review of the literature is presented with the retrieval of the main published articles, as well as an analysis of the dimensionality of the construction, all the definitions found in the literature. In addition, an improvement in the definition of frugal innovation is proposed through the creation of a frugal ecosystem. All procedures follow the steps based on the Churchill paradigm (Churchill 1979) which was updated by Mackenzie, Podsakoff and Podsakoff (2011). In the first stage, 66 items were generated based on a broad literature review. Content validation was performed through personal interviews with 12 experts (academics and managers), resulting in 20 items retained. Afterwards, the face validation was performed with 22 managers aiming to improve the clarity and understanding of the items, resulting in 12 items retained. With the 12 items, a survey was performed composed of 191 Brazilian companies, where a Factorial Exploratory Analysis (EFA) was carried out as a first purification process, in which all the statistical indices were adjusted. As a result three dimensions were obtained (1) Focus on core functionality and performance; (2) Substantial cost reduction; and (3) Creation of a Frugal Ecosystem, all composed of 9 items, three items in each dimension. A second round of research was conducted with 247 Brazilian companies, and with these data a Confirmation Factor Analysis (CFA) and internal consistency verification were performed, where all adjustments were obtained again. The questionnaire was subjected to subsequent translation procedures to reach the validity of the translation and then two more surveys were conducted with 250 American companies and 300 Indian companies for final validation purposes. As a result, other validations were obtained, such as convergent viability, discriminant validity, reliability verification and nomological validity (through the application of other scales). The scale was applied to Indian companies in order to obtain results from another emerging country. Contributing to the discussion about frugal innovation is not only appropriate for emerging countries or is also a phenomenon that may occur in developed countries, this scale has also been applied with US companies. With this scale validated, this study contributes to other researches, allowing results from other countries, developed or in the process of development, for comparative research and for a better understanding of the relationships of Frugal innovation with other phenomena.